2002
DOI: 10.1093/jac/dkf032
|View full text |Cite
|
Sign up to set email alerts
|

In vitro bactericidal activity and post-antibiotic effect of ABT-773 versus co-amoxiclav against anaerobes

Abstract: In vitro bactericidal activity and post-antibiotic effect of ABT-773 versus co-amoxiclav against anaerobes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Previous studies have suggested that compounds which exhibited <3 log 10  CFU/ml reduction from initial CFU count at 24 h indicated a bacteriostatic effect while compounds that displayed ≥3 log 10  CFU/ml reduction from initial CFU count at 24 h indicated a bactericidal action against the tested microbe/s [17, 18]. Results of this time-kill study corroborated with previous MBC/MIC ratio values [1] that suggested MFM501 has a bacteriostatic mechanism of action against MRSA and MSSA isolates.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have suggested that compounds which exhibited <3 log 10  CFU/ml reduction from initial CFU count at 24 h indicated a bacteriostatic effect while compounds that displayed ≥3 log 10  CFU/ml reduction from initial CFU count at 24 h indicated a bactericidal action against the tested microbe/s [17, 18]. Results of this time-kill study corroborated with previous MBC/MIC ratio values [1] that suggested MFM501 has a bacteriostatic mechanism of action against MRSA and MSSA isolates.…”
Section: Discussionsupporting
confidence: 85%
“…This model further discovered that resistant strains of Bacteroides fragilis emerged when the area under the concentration-time curve from 0 to 24 h (AUC 24 )-to-MIC ratio was less than 40 (26). In time-kill assays, maximal bactericidal activity against various anaerobes (B. fragilis, B. thetaiotaomicron, Peptostreptococcus magnus, and Clostridium perfringens) was observed at twice the MIC with levofloxacin (25). These in vitro investigations suggest that relatively low, prolonged concentrations of newer fluoroquinolones have the ability to eradicate susceptible anaerobic organisms.…”
mentioning
confidence: 99%